Reforma y contrarreforma laboral en Argentina, crónica simple de un proceso pendular - Goldin, Adrián (2012)
Labor reform and counter-reform in Argentina, simple chronic of a pendulum processAfter placing it in the context of the processes of labor reforms produced in Latin America in the early 90’s (its inspiration, its dynamics, its actors), the article considers in particular the case of Argentina. Inthat assignment, it examines the labor reforms that took place there from dominant perspectives - external flexibility, internal flexibility, reduction and variation of costs, collective labor relations - confirming a strong deregulated activism in the field of individual relations, while it was verified a high administrative interventionism of decentralized bias with a limited institutional transformation in collective relations.At the end of that decade, it had already been clear that those strategies haven’t had a virtuous effect on the social labor situation or the labor market. In this context, a new government that comes into power in 2003, leaves without effect a good part of those reforms and instead it undertakes a process of institutional reconfiguration of the legal system of labor protection: a systematic increase of the Living Wage, strengthening of the collective wage bargaining - with the consequent tendential improvement of wages of workers in the formal sector - and, by virtue of parliamentary initiatives, a sequence of introduction of micro-reforms always oriented to increase the protection of workers, which as a whole would have to involve a remarkable recovery of the tutelary bias of labor regulations.